Sustainability assessment of alluvial and open pit mining systems in Colombia: life cycle assessment, exergy Analysis, and emergy accounting (2018)
In this doctoral thesis the sustainability of two mining systems in Colombia is evaluated; open-pit and alluvial mining from cradle to gate, through the implementation of environmental, social and / or economic indicators provided by Life Cycle Assessment (LCA), Exergy Analysis, and Emergy Accounting. Stages of the process that generate greater environmental impacts, exergy losses, and lower overall emergy efficiency in the entire productive chain are identified to decide where to put efforts in order to optimize systems in the most efficient way. Finally, complementarity or redundancy of results obtained by the three methodologies is identified as a tool to inform decision making in mining sector. An integration methodology for sustainability assessment is proposed, in which a unified performance metric (Integrated Sustainability Index) is obtained to evaluate Triple Bottom Line - TBL throughout the mining production process, which can be implemented in other production systems. This index presents a comprehensible hierarchical structure built by support methodologies such as LCA, Emergy, and Exergy, which have regulatory and academic validity. All of this with the aim of providing a useful analysis tool to policy makers for the proposal of improvements, changes and key elements for the economic, energy, and especially environmental optimization of the process. LCA evaluates process sustainability based on the environmental impacts generated by waste and emissions released to the environment; Emergy based on the use of the necessary resources to carry out the process, and Exergy based on process efficiency. Based on this, Open-pit mining presents higher values in human health damage category, whereas alluvial mining causes more damage on ecosystem quality. In emergy terms, both extractive systems present a high dependence on imported non-renewable resources, which makes processes less sustainable in the long term. Exergetically, both mining processes, especially Open-pit, are considered as anti-exergy, since there is a decrease of exergy between the initial state of input and end of output, producing waste with a high exergy content. However, the market price of gold is the one that internalizes the externalities generated in the process, bearing exergy losses and, in turn, allowing to recover the natural and human capital invested. Results of the proposed integration method show that alluvial mining presents a better environmental and social behaviour, while open-pit mining does it in the economic dimension. Process sustainability can be improved by the efficient use of resources, optimization of exergy efficiency and, decreasing the consumption of non-renewable resources, replacing them with local renewable resources especially in tails and extraction stage in open-pit mining, stripping and benefit stage in alluvial mining.